Knowledge, Attitude and Practice of nursing students on Hospital Acquired Infections in Western region of Nepal - Paudel, Ishwari Sharama; Ghosh, Vivek; Adhikari, Purushottam (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Hospital-acquired infections (HAIs) are a common problem and challenge faced by hospitals in all countries around the world. Nurses are an important part of the healthcare team that plays a unique role in the control of HAIs. Compliance on the part of healthcare workers (HCWs) including nurses with standard precautions has been recognized as being an efficient means to prevent and control HAIs. The present study was conducted with objective of understanding the level of Knowledge, attitude and practice (KAP) regarding HAIs among nursing students in the Western Region of Nepal. Materials & Methods: This descriptive cross-sectional study was conducted among nursing students posted in different wards of two hospitals of Pokhara. A self administered questionnaire containing different set of questions regarding knowledge, attitude and practice on HAI were used for data collection. Results: Among the total participants in the study 97% of the participants considered that prevention of HAIs were a valuable part of nurses’ role but only 89% had received formal training regarding hand hygiene. The results show that 74% of the participants had good knowledge regarding HAIs. 82% of the participants felt that they would be less likely to transmit infection to the patient if they performed hand-hygiene. 66% of them identified that hand hygiene agents were not readily available in current settings. Regarding practice, only 6% performed hand hygiene before patient contact. Conclusion: The nursing students had good knowledge regarding HAIs that was reflected in their attitude and practice on hand hygiene for the prevention of HAIs. However there is the need of regular training and performance feedback regarding hand hygiene and the hospital environment should be hand-hygiene friendly with easily accessible to sinks and other facilities.